(untitled) (International Journal of Engineering and Computer Science, 2017)
Data Mining extracts required information from large dataset. The Key Concept of Data mining is to classify the desired data according to posterior probability. It utilizes data classification and prediction technique generating students rank list for college admission is an important risk in all the institution eligible students for particular discipline is evaluated based on specified constraints here risk evaluation and prediction is performed which allows the user to generate the risk predicting and determine whether seats can be granted or not. This paper concentrates mainly the concept of multidimensional data classification and clustering for predicting the risks